Inequalities in Maternal Complications in Indonesia: A Multilevel Analysis of Education, Parity, and Health Insurance using IFLS 2014/2015 - Pertiwi, Dwi Nofiana Gita (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2025)
Maternal complications remain a critical challenge in Indonesia, where progress toward the SDGs target of reducing maternal mortality has been slow. This study investigates how education and the absence of health insurance shape complication risks. Using nationally representative data from the IFLS (2014/15), we analyzed 6,156 women’s last pregnancies across 20 provinces. Multilevel logistic regression models were estimated, with predictive margins used to explore education with parity and insurance interactions. Women with primary or less education had significantly higher odds of complications than those with post-secondary education (OR=1.41, 95% CI). Predictive margins revealed that education reduced risks at higher parities, while first births carried elevated risks across all education groups. Insurance effects were uneven: women covered by government schemes (JKN, Jampersal) had greater odds of complications (OR=1.32 and OR=1.36), while those with employer/private insurance showed lower risks (OR=0.61). Older maternal age (≥35 years) increased risks, whereas antenatal care visits did not show a consistent protective effect. These findings emphasized that education and health insurance remain crucial for maternal complications in Indonesia. Policies should therefore prioritize first-time and high-parity mothers with low education, while also strengthening JKN to deliver equitable services, so that women without private insurance are not systematically disadvantaged.